Functionalized Polyelectrolytes Assembling on Nano‐BioFETs for Biosensing Applications. (4th March 2015) - Duan, Xuexin; Mu, Luye; Sawtelle, Sonya D.; Rajan, Nitin K.; Han, Ziyu; Wang, Yanyan; Qu, Hemi; Reed, Mark A.
Abstract : A new surface functionalization scheme for nano‐Bio field effect transistors (FETs) using biocompatible polyelectrolyte thin films (PET) is developed. PET assemblies on Si nanowires (Si‐NWs) are driven by electrostatic interactions between the positively charged polymer backbone and negatively charged Si/SiO2 surface. Such assemblies can be directly coated from PET aqueous solutions and result in a uniform nanoscale thin film, which is more stable compared to the conventional amine silanization. Short oligo‐ethylene glycol chains are grafted on the PETs to prevent nonspecific protein binding. Moreover, the reactive groups of the polymer chains can be further functionalized to other chemical groups in specific stoichiometry for biomolecules detection. Therefore, it opens a new strategy to precisely control the functional group densities on various biosensor surfaces at the molecular level. In addition, such assemblies of the polymers together with the bound analytes can be removed with the pH stimulation resulting in regeneration of a bare sensor surface without compromising the integrity and performance of the Si‐NWs. Thus, it is believed that the developed PET coating and sensing systems on Si‐NW FETs represent a versatile, promising approach for regenerative biosensors which can be applied to other biosensors and will benefit real device applications, enhancing sensor lifetime, reliability, and repeatability. Abstract : Functionalized polyelectrolytes are successfully synthesized and assembled on silicon nanowire field effect transistors with the aim of creating regenerative nano‐electronic biosensors. Such coating has the advantage of direct solution coating and can be applied on a wafer scale. It minimizes protein nonspecific adsorption and precisely controls the surface functional group densities at molecular level.